C / C-SiC composite material for airplane air inlet duct component and preparation method thereof
By introducing the PyC interface layer and two-stage graphitization treatment in the preparation process of C/C-SiC composite materials, and sintering them in a graphite crucible embedded in silicon powder for sintering, the problem of prone to performance damage in the prior art C/C-SiC composite materials is solved, and the strength, thermal conductivity and life are improved.
Patent Information
- Application Number
- CN202510090547.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-05-02
AI Technical Summary
In the prior art, C/C-SiC composites are prone to performance damage during subsequent processing, resulting in increased scrap rate and increased cost.
By introducing the carbon fiber preform into the PyC interface layer and two-stage graphitization treatment, C/C porous body 2 was obtained and placed in a graphite crucible embedded in silicon powder for sintering to produce an improved performance C/C-SiC composite material.
It improves the strength, thermal conductivity and life of C/C-SiC composite materials, and reduces the performance damage and cost of subsequent processing.
Smart Images

Figure CN119912270A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of composite materials, and in particular to a C / C-SiC composite material for aircraft air inlet components and a preparation method thereof. Background Art
[0002] Fighter jets are generally powered by aviation gas turbine engines, which work by inhaling air, compressing, and igniting mixed fuel to produce high-temperature and high-pressure gas, and then using the energy in the gas to drive the engine to operate and generate thrust. There is a very critical step in the entire working process, which is "inhaling air". In order to make the engine work stably and efficiently, an air intake device is required. With the continuous improvement of the performance requirements of aviation engines, higher requirements are placed on the lightweight, high temperature resistance, mechanical properties, and thermal insulation properties of materials.
[0003] Carbon fiber reinforced silicon carbide (C / C-SiC) composite materials have the advantages of low density, high specific strength, high specific modulus, wear resistance, corrosion resistance, and long service life. They are a type of advanced composite materials developed on the basis of C / C composite materials and can be used to prepare complex structural components used in aviation, aerospace, military industry, nuclear energy and other fields. They are prepared by repeated densification of carbon fiber preforms through chemical vapor deposition or ceramic precursor impregnation-cracking processes; the performance of the composite materials is easily damaged during subsequent processing, resulting in an increase in scrap rate and cost. Summary of the invention
[0004] The purpose of the present invention is to provide a C / C-SiC composite material for aircraft air intake components and a preparation method thereof, wherein a carbon fiber preform is introduced with a PyC interface layer and subjected to a two-stage graphitization treatment to obtain a C / C porous body 2, and then sintered after being embedded with silicon powder to obtain a C / C-SiC composite material with improved performance, thereby solving the problems of easy performance damage and high scrap rate in the prior art.
[0005] In order to solve the above technical problems, the present invention adopts the following solutions:
[0006] A method for preparing a C / C-SiC composite material for an aircraft air intake component comprises the following steps:
[0007] S1, continuously laying a first carbon fiber layer and a second carbon fiber layer to obtain a carbon fiber preform;
[0008] S2, introducing a PyC interface layer into a carbon fiber preform by chemical vapor infiltration to obtain a C / C porous body 1;
[0009] S3, subjecting the C / C porous body 1 to a two-stage graphitization treatment to obtain a C / C porous body 2;
[0010] S4, placing the C / C porous body 2 in a graphite crucible loaded with silicon powder for ceramic treatment to obtain a C / C-SiC composite material.
[0011] Furthermore, in step S1, after continuous layering, needle punching is performed layer by layer, and the needle punching density is 2.0 to 2.5 needles / cm 2 .
[0012] The needle-punched fiber is formed by pulling the short fibers of the web layer toward the Z direction through needle punching, forming a "human" shape. It has a certain promoting effect on the densification of the reactive infiltration of C / C-SiC composite materials during the reactive infiltration process, improves the strength performance of silicon carbide ceramic composite materials, and makes the composite materials lighter.
[0013] Furthermore, the number of monofilaments in the first carbon fiber layer is 3K polyacrylonitrile-based carbon fiber, and the number of monofilaments in the second carbon fiber layer is 12K polyacrylonitrile-based carbon fiber.
[0014] Furthermore, in step S2, propylene and nitrogen are used as carbon source gases, nitrogen dilution gas and argon are used as protective gases, the flow ratio of propylene to nitrogen is 3:1, the deposition pressure is 0.5-0.6 KPa, the deposition temperature is 850°C, the deposition time is 120-160 hours, and the number of depositions is 4-6 times.
[0015] Furthermore, the temperature of the primary graphitization treatment is 2000-2200° C., the atmosphere is argon, the heating rate is 5-10° C. / min; and the insulation time is 5-15 min.
[0016] Furthermore, the temperature of the secondary graphitization treatment is 2600-2800° C., the atmosphere is argon, the heating rate is 5-10° C. / min; and the holding time is 5-10 min.
[0017] The C / C porous body is subjected to two-stage graphitization treatment at high temperature to make its graphitization degree higher, so that the finally prepared C / C-SiC has high thermal conductivity.
[0018] Furthermore, the density of the C / C porous body 2 is 1.30-1.35 g / cm 3 .
[0019] Further, in step S4, the C / C porous body 2 is placed in a silicified graphite crucible, and the graphite crucible is placed in a sintering furnace by an embedding method, filled with argon as a protective gas, and the pressure in the furnace is 10-15 KPa. The sintering furnace is heated to 1750°C and kept warm for 6 hours to obtain a density of 1.90-1.95 g / cm 3C / C-SiC composite material. The C / C porous body is placed in a silicified graphite crucible and embedded with high-purity silicon powder, and infiltrated in a high-temperature sintering furnace to obtain a C / C-SiC composite material. A ceramic-based composite material can be prepared that can quickly increase density, withstand high temperatures of 1200°C, have certain thermal insulation properties and good mechanical properties.
[0020] Furthermore, the silicon powder has a particle size of 74 μm and a purity of 99.99%.
[0021] A C / C-SiC composite material is prepared by adopting the above-mentioned method for preparing a C / C-SiC composite material for aircraft air inlet components.
[0022] The beneficial effects of the present invention are as follows: the present invention lays a certain number of carbon fiber layers 1 and 2 and needle punches them layer by layer to obtain a carbon fiber preform with fewer upper and lower warp and weft pores and more center warp and weft pores. The C / C porous body 2 is obtained by chemical vapor infiltration and two-stage graphitization treatment, and the C / C porous body 2 is placed in a silicified graphite crucible and embedded with high-purity silicon powder, and infiltrated in a high-temperature sintering furnace to obtain 1.90-1.95g / cm 3 , a C / C-SiC composite material with a room temperature tensile strength of 300 to 320 MPa improves the strength, thermal conductivity and life of the C / C-SiC composite material, reduces performance damage in subsequent processing, and reduces costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The schematic diagram of the preparation process of this method is shown in FIG. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described below in conjunction with the drawings of the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, not all of the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] In all examples shown and discussed herein, any specific values should be interpreted as merely exemplary and not as limiting. Therefore, other examples of the exemplary embodiments may have different values.
[0026] Example 1
[0027] A method for preparing a C / C-SiC composite material for aircraft air intake components, such as Figure 1 As shown, the following steps are included:
[0028] (1) HTS-3K polyacrylonitrile-based carbon fiber from Toho Co., Ltd. of Japan was used as the first carbon fiber layer, and T700-12K polyacrylonitrile-based carbon fiber from Toray Co., Ltd. of Japan was used as the second carbon fiber layer. The first carbon fiber layer and the second carbon fiber layer were continuously laid 10 layers, and needle-punched layer by layer, with a needle-punching density of 2.0 needles / cm 2 A carbon fiber preform was obtained with a thickness of 3.8 mm.
[0029] (2) A PyC interface layer was introduced into the carbon fiber preform by chemical vapor infiltration, propylene (99.9%) and nitrogen were used as carbon source gases, nitrogen (99.9%) dilution gas and argon (99.9%) were used as protective gases, the flow ratio of propylene to nitrogen was 3:1, the deposition pressure was 0.6 KPa, the deposition temperature was 850 ° C, the deposition time was 120 h, the deposition times were 6 times, and a C / C porous body was obtained by deposition in a chemical vapor deposition furnace;
[0030] (3) The C / C porous body is first subjected to a primary graphitization treatment at a temperature of 2000°C, an argon atmosphere, a heating rate of 5°C / min, and a holding time of 5 min;
[0031] Then, two-stage graphitization treatment was performed at a temperature of 2600°C, an argon atmosphere, a heating rate of 10°C / min, and a holding time of 10 min to obtain a C / C porous body 2 with a density of 1.30 g / cm 3 .
[0032] (4) The C / C porous body 2 is placed in a silicified graphite crucible, and the graphite crucible is loaded with silicon powder with a particle size of 74 μm and a purity of 99.99%. The graphite crucible is placed in a sintering furnace using an embedding method, filled with argon as a protective gas, and the pressure in the furnace is 15 KPa. The sintering furnace is heated to 1750°C and kept warm for 6 hours to obtain a C / C-SiC composite material. The final density of the C / C-SiC composite material is 1.95 g / cm 3 , room temperature flexural strength 500MPa, room temperature tensile strength 320MPa, room temperature fracture toughness 26.4MPa·m 1 / 2 Its flame cycle life is 21,000 times at 1,200°C, and its thermal shock life is 21,000 times at 1,000°C.
[0033] Example 2
[0034] A method for preparing a C / C-SiC composite material for an aircraft air intake component comprises the following steps:
[0035] (1) HTS-3K polyacrylonitrile-based carbon fiber from Toho Corporation of Japan was used as the first carbon fiber layer, and T700-12K polyacrylonitrile-based carbon fiber from Toray Corporation of Japan was used as the second carbon fiber layer. The first carbon fiber layer and the second carbon fiber layer were continuously laid 10 layers, and needle-punched layer by layer, with a needle-punching density of 2.5 needles / cm 2 A carbon fiber preform was obtained with a thickness of 3.8 mm.
[0036] (2) A PyC interface layer was introduced into the carbon fiber preform by chemical vapor infiltration, propylene (99.9%) and nitrogen were used as carbon source gases, nitrogen (99.9%) dilution gas and argon (99.9%) were used as protective gases, the flow ratio of propylene to nitrogen was 3:1, the deposition pressure was 0.6 KPa, the deposition temperature was 850 ° C, the deposition time was 160 h, the deposition times were 4 times, and a C / C porous body was obtained by deposition in a chemical vapor deposition furnace;
[0037] (3) The C / C porous body is first subjected to a primary graphitization treatment at a temperature of 2000°C, an argon atmosphere, a heating rate of 8°C / min, and a holding time of 10 min;
[0038] Then, two-stage graphitization treatment was performed at a temperature of 2800 °C, an argon atmosphere, a heating rate of 8 °C / min, and a holding time of 14 min to obtain a C / C porous body 2 with a density of 1.32 g / cm 3 .
[0039] (4) The C / C porous body 2 is placed in a silicified graphite crucible, and the graphite crucible is loaded with silicon powder with a particle size of 74 μm and a purity of 99.99%. The graphite crucible is placed in a sintering furnace using an embedding method, filled with argon as a protective gas, and the pressure in the furnace is 15 KPa. The sintering furnace is heated to 1750°C and kept warm for 6 hours to obtain a C / C-SiC composite material. The final density of the C / C-SiC composite material is 1.95 g / cm 3 , room temperature flexural strength 450MPa, room temperature tensile strength 300MPa, room temperature fracture toughness 25.0MPa·m 1 / 2 . Its flame cycle life is 22,000 times at 1,200°C, and its thermal shock life is 20,000 times at 1,000°C.
[0040] Example 3
[0041] A method for preparing a C / C-SiC composite material for an aircraft air intake component comprises the following steps:
[0042] (1) HTS-3K polyacrylonitrile-based carbon fiber from Toho Co., Ltd. of Japan was used as the first carbon fiber layer, and T700-12K polyacrylonitrile-based carbon fiber from Toray Co., Ltd. of Japan was used as the second carbon fiber layer. The first and second carbon fiber layers were laid in 8 layers in succession, and needle-punched layer by layer, with a needle-punching density of 2.4 needles / cm 2 A carbon fiber preform was obtained with a thickness of 3.6 mm.
[0043] (2) A PyC interface layer was introduced into the carbon fiber preform by chemical vapor infiltration, propylene (99.9%) and nitrogen were used as carbon source gases, nitrogen (99.9%) dilution gas and argon (99.9%) were used as protective gases, the flow ratio of propylene to nitrogen was 3:1, the deposition pressure was 0.5 KPa, the deposition temperature was 850 ° C, the deposition time was 150 h, the deposition times were 5 times, and a C / C porous body was obtained by deposition in a chemical vapor deposition furnace;
[0044] (3) The C / C porous body is first subjected to a primary graphitization treatment at a temperature of 2100°C, an argon atmosphere, a heating rate of 8°C / min, and a holding time of 15 min;
[0045] Then, two-stage graphitization treatment was performed at a temperature of 2700°C, an argon atmosphere, a heating rate of 5°C / min, and a holding time of 5 min to obtain a C / C porous body 2 with a density of 1.35 g / cm 3 .
[0046] (4) The C / C porous body 2 is placed in a silicified graphite crucible, and the graphite crucible is loaded with silicon powder with a particle size of 74 μm and a purity of 99.99%. The graphite crucible is placed in a sintering furnace using an embedding method, filled with argon as a protective gas, and the pressure in the furnace is 10 KPa. The sintering furnace is heated to 1750°C and kept warm for 6 hours to obtain a C / C-SiC composite material. The final density of the C / C-SiC composite material is 1.90 g / cm 3 , room temperature flexural strength 510MPa, room temperature tensile strength 320MPa, room temperature fracture toughness 25.8MPa·m 1 / 2 Its flame cycle life is 20,000 times at 1200°C, and its thermal shock life is 22,000 times at 1000°C.
[0047] The above description is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been disclosed as a preferred embodiment as above, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a C / C-SiC composite material for aircraft air intake components, characterized in that: The following steps are involved: S1, continuously laying a first carbon fiber layer and a second carbon fiber layer to obtain a carbon fiber preform; S2, introducing a PyC interface layer into a carbon fiber preform by chemical vapor infiltration to obtain a C / C porous body 1; S3, subjecting the C / C porous body 1 to a two-stage graphitization treatment to obtain a C / C porous body 2; S4, placing the C / C porous body 2 in a graphite crucible loaded with silicon powder for ceramic treatment to obtain a C / C-SiC composite material.
2. The method for preparing a C / C-SiC composite material for aircraft air intake components according to claim 1, characterized in that: In step S1, after continuous layering, needle punching is performed layer by layer, and the needle punching density is 2.0 to 2.5 needles / cm 2 .
3. The method for preparing a C / C-SiC composite material for aircraft air intake components according to claim 1, characterized in that: The number of monofilaments in the first carbon fiber layer is 3K polyacrylonitrile-based carbon fiber, and the number of monofilaments in the second carbon fiber layer is 12K polyacrylonitrile-based carbon fiber.
4. The method for preparing a C / C-SiC composite material for aircraft air intake components according to claim 1, characterized in that: In step S2, propylene and nitrogen are used as carbon source gases, nitrogen dilution gas and argon are used as protective gases, the flow ratio of propylene to nitrogen is 3:1, the deposition pressure is 0.5-0.6 KPa, the deposition temperature is 850°C, the deposition time is 120-160 hours, and the number of depositions is 4-6 times.
5. The method for preparing a C / C-SiC composite material for aircraft air intake components according to claim 1, characterized in that: The temperature of the primary graphitization treatment is 2000-2200° C., the atmosphere is argon, the heating rate is 5-10° C. / min; and the insulation time is 5-15 min.
6. The method for preparing a C / C-SiC composite material for aircraft air intake components according to claim 1, characterized in that: The temperature of the secondary graphitization treatment is 2600-2800° C., the atmosphere is argon, the heating rate is 5-10° C. / min; and the holding time is 5-10 min.
7. The method for preparing a C / C-SiC composite material for aircraft air intake components according to claim 1, characterized in that: The density of the C / C porous body 2 is 1.30-1.35 g / cm 3 .
8. The method for preparing a C / C-SiC composite material for aircraft air intake components according to claim 1, characterized in that: In step S4, the C / C porous body 2 is placed in a silicified graphite crucible, and the graphite crucible is placed in a sintering furnace by an embedding method, filled with argon as a protective gas, and the pressure in the furnace is 10-15 KPa. The sintering furnace is heated to 1750°C and kept warm for 6 hours to obtain a density of 1.90-1.95 g / cm 3 C / C-SiC composites.
9. The method for preparing a C / C-SiC composite material for aircraft air intake components according to claim 8, characterized in that: The silicon powder has a particle size of 74 μm and a purity of 99.99%.
10. A C / C-SiC composite material, characterized in that: The method for preparing a C / C-SiC composite material for an aircraft air inlet component according to any one of claims 1 to 9 is used.